Clinical assessment determines the diagnosis of inclusion body myositis independently of pathological features. - Brady, S; Squier, W; Hilton-Jones, D (2013)
BACKGROUND AND OBJECTIVE: Historically, the diagnosis of sporadic inclusion body myositis (IBM) has required the demonstration of the presence of a number of histopathological findings on muscle biopsy--namely, rimmed vacuoles, an inflammatory infiltrate with invasion of non-necrotic muscle fibres (partial invasion) and amyloid or 15-18 nm tubulofilamentous inclusions (Griggs criteria). However, biopsies of many patients with clinically typical IBM do not show all of these histopathological findings, at least at presentation. We compared the clinical features at presentation and during the course of disease in 67 patients with histopathologically diagnosed IBM and clinically diagnosed IBM seen within a single UK specialist muscle centre. METHODS AND RESULTS: At presentation, using clinically focused diagnostic criteria (European Neuromuscular Centre (ENMC) 2011), a diagnosis of IBM was made in 88% of patients whereas 76% fulfilled the 1997 ENMC criteria and only 27% satisfied the histopathologically focused Griggs criteria. There were no differences in clinical features or outcomes between clinically and histopathologically diagnosed patients, but patients lacking the classical histopathological finding of rimmed vacuoles were younger, suggesting that rimmed vacuoles may be a later feature of the disease. CONCLUSIONS: These findings have important implications for diagnosis and future studies or trials in IBM as adherence to histopathologically focused diagnostic criteria will exclude large numbers of patients with IBM. Importantly, those excluded may be at an earlier stage of the disease and more amenable to treatment.